2011
DOI: 10.4103/0019-509x.82879
|View full text |Cite
|
Sign up to set email alerts
|

Prostate biopsy findings in Indian men: A hospital-based study

Abstract: Cancer is less common and inflammatory lesions more common at all levels of PSA in our patients. The effect of antibiotics on PSA and biopsy in our patients needs to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…Bikkasani K et al found 20.7% cases with Gleason score of 8-10 in their study. 12 Similarly, Gleason score of 7 was seen in 51.6% and 15% cases respectively in studies done by Jaypradeep DP et al and Carter HB et al 2,17 The reason for high Gleason score in our study could be due to the late presentation of the disease. The rate of change in PSA appears to be greater in men with prostate carcinoma compared with men without disease.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Bikkasani K et al found 20.7% cases with Gleason score of 8-10 in their study. 12 Similarly, Gleason score of 7 was seen in 51.6% and 15% cases respectively in studies done by Jaypradeep DP et al and Carter HB et al 2,17 The reason for high Gleason score in our study could be due to the late presentation of the disease. The rate of change in PSA appears to be greater in men with prostate carcinoma compared with men without disease.…”
Section: Discussionsupporting
confidence: 69%
“…1 Similarly other studies also showed that PSA level is usually < 20 ng/ ml in case of benign conditions like BPH. 12,13 Prostatic intraepithelial neoplasia was seen in 5.9 % cases in our study and all the cases were HGPIN with PSA level <10ng/ml. The studies done in two different parts of India showed similar finding (1.8% cases of PIN in each study) and the PSA level was <10 ng/ml.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…19 In current study we detect prostate pathology in 112 cases aged between 34 -81 years with mean age of 58+3.4 years, these findings were also observed by other workers. 19,20 Confirming the documented data we observed hyperplasia in 99 (82.1%) cases and among them 6.3% cases were with prostatitis, the hyperplasia was common in 61-70 years age group. 9,19 We histologically diagnose 4.4% cases of adenocarcinoma from a total of 112 cases, the reported data incidence is 3.1%, 4.8% and 6.9% in different studies.…”
Section: Discussionsupporting
confidence: 86%
“…Figure 2 shows an immunostaining of carcinogenic PAH-DNA adducts in the peripheral zone of cancer-free prostates from the U.K. and India stained with antiserum specific for a family of carcinogenic PAHs bound to DNA, and semi-quantified by the Automated Cellular Imaging System (ACIS) [ 83 ]. The prostate tissues from India were obtained at a time (2008–2010) when radical retropubic prostatectomy was a rare procedure in this region [ 84 ]. While Figure 2B shows a marked interindividual variation in adduct levels, there is a relatively similar range of PAH-DNA adduct levels in the prostates from both groups.…”
Section: Prostate Cancer and Carcinogenic Pah Exposurementioning
confidence: 99%